2x(x-1)=5(x+3)

Simple and best practice solution for 2x(x-1)=5(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x-1)=5(x+3) equation:


Simplifying
2x(x + -1) = 5(x + 3)

Reorder the terms:
2x(-1 + x) = 5(x + 3)
(-1 * 2x + x * 2x) = 5(x + 3)
(-2x + 2x2) = 5(x + 3)

Reorder the terms:
-2x + 2x2 = 5(3 + x)
-2x + 2x2 = (3 * 5 + x * 5)
-2x + 2x2 = (15 + 5x)

Solving
-2x + 2x2 = 15 + 5x

Solving for variable 'x'.

Reorder the terms:
-15 + -2x + -5x + 2x2 = 15 + 5x + -15 + -5x

Combine like terms: -2x + -5x = -7x
-15 + -7x + 2x2 = 15 + 5x + -15 + -5x

Reorder the terms:
-15 + -7x + 2x2 = 15 + -15 + 5x + -5x

Combine like terms: 15 + -15 = 0
-15 + -7x + 2x2 = 0 + 5x + -5x
-15 + -7x + 2x2 = 5x + -5x

Combine like terms: 5x + -5x = 0
-15 + -7x + 2x2 = 0

Factor a trinomial.
(-3 + -2x)(5 + -1x) = 0

Subproblem 1

Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5

Subproblem 2

Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5

Solution

x = {-1.5, 5}

See similar equations:

| 2x^3-11x^2+22x-15=0 | | 5x+31=14x-92 | | 945000+x=10x | | X^3-2x^2+3x+4=0 | | 5x-3(x-2)=30-3(x+3) | | 0.2x^2-80x+2500=0 | | 2t=34 | | 19x-17=3(4x-13) | | E+5=25 | | 6x-11y=0 | | 0=(12x^2)+6x-18 | | 7x+2y=-15 | | t-11+3= | | 24d+12x+8d-12x= | | 10x-3y=43 | | x+7y=-36 | | 2x=b+1-ax | | x-7y=34 | | 6x+6-2x=0 | | 6-7a-5a^2=0 | | 8-(1-2m)=8+2(4m-3) | | 3x^4+4x^2+28x+5=0 | | 11x+7=4x+56 | | 5(x+3)-2=2-x+9 | | 2y^2-8y=540 | | 8x-5y=-37 | | 4m+100=68 | | ln(7-3x)=7.5 | | -6-2n=48 | | V^2=4v-13 | | 5=15x-12y | | 7x-y=66 |

Equations solver categories